Smith, Wordsworth, and the Model of the Romantic Poet - Labbe, Jacqueline (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractThis essay examines how Charlotte Smith and William Wordsworth manipulate the autobiographical and elements of poetical voicing as they explore the figure of the Romantic Poet. Focusing on Beachy Head (1807) and The Prelude (1805), I suggest that in devising separate, competing but eventually equal “personal” voices in Beachy Head, and in interrogating tropes of genre and composition in The Prelude, the two poets signal their interest in using poetry to provide an answer to Wordsworth’s famous question, “What is a Poet?” For each, the model of the Romantic poet is most viable when, like wet clay, it is still able to be shaped.